Impact of Adverse Events on the Progression-Free Survival of Patients with Advanced Hepatocellular Carcinoma Treated with Lenvatinib: A Multicenter Retrospective Study - Takamasa Ohki; Koki Sato; Mayuko Kondo; Eriko Goto; Takahisa Sato; Yuji Kondo; Masatoshi Akamatsu; Shinpei Sato; Hideo Yoshida; Yukihiro Koike; Shuntaro Obi (Adis, Springer Healthcare, 2020)
Abstract Background and Objective Experience of the use of lenvatinib (LEN) in the clinical setting remains limited. We conducted this study to elucidate the factors associated with progression-free survival (PFS) in patients with advanced HCC treated with LEN. Methods In this multicenter retrospective study, we analyzed data on patient characteristics, treatment outcomes, and adverse events (AEs) for 77 patients with advanced hepatocellular carcinoma (HCC). We also analyzed PFS and factors that influence PFS. Results The response rate to LEN was 29.9% and the disease control rate was 77.9%. Patients who achieved relative dose intensities of more than 70% had better outcomes (response rate 45.2% vs. 11.4%, P < 0.01). Appetite loss, fatigue, diarrhea, hypertension, and thyroid dysfunction were the most frequent AEs. Twenty-three patients (29.9%) had grade 3 or 4 AEs. Fifty-two patients (67.5%) required a dose reduction and 47 (61.0%) stopped taking the drug due to AEs. The PFS rates at 3, 6, and 12 months were 81.2%, 49.8%, and 34.8%, respectively. The median PFS was 5.6 months. Multivariate analysis showed that thyroid dysfunction of grade ≥ 2 (hazard ratio [HR] 4.57, 95% confidence interval [CI] 2.05-10.2, P < 0.01), appetite loss (HR 3.58, 95% CI 1.72-7.52, P < 0.01), and tumor diameter ≥ 40 mm (HR: 2.27, 95% CI 1.17-4.40, P = 0.015) were independent factors associated with poor PFS. On the other hand, Child-Pugh class 5A (HR 0.41, 95% CI 0.19-0.90, P = 0.027) and complete or partial response (HR 0.40, 95% CI 0.17-0.95, P = 0.039) were independent factors associated with better PFS. Conclusions Thyroid dysfunction and appetite loss after the administration of LEN were independent factors associated with shorter PFS, so these AEs should be carefully managed after administering LEN.